Relationship with place: a transformative and sustainable pedagogy for the planet - Julie Singleton (Academia Environmental Sciences and Sustainability)
The central hypothesis of this conceptual commentary is that place-based educational approaches that use local environments as the learning context could not only provide needed educational reforms but also sow the seeds of sustainable behaviors of future generations. Furthermore, natural environments are offered as an optimal context for the emotional and sensory-rich needs of learning experiences that transform eco-paradigms and develop land ethics. The supporting literature examines the nexus of environmental education, place-based approaches, benefits of nature experience, and transformational learning. Breaking barriers of current economic, political, and educational institutions requires integrative approaches—head, hand, and heart—to transform eco-paradigms. A conceptual diagram is offered to visualize this holistic approach. The rich context of a natural place enhances the esthetic quality of a learning experience and is dependent on the relationships within the community of learners, sensory interaction with the learning context or place, the emotion that arouses, thoughts derived from reflection on the experience, and the depth of engagement and behavior change that ensues. I support the power of place as a learning context through personal narrative. Although place-based education can be applied in any community and educational setting, I offer my own cultural perspective as an American with a critique of the consumer culture of the place in which I reside and the effect of rigid institutions on eco-values. Place-based educational reforms could develop caring for local environments leading to young people striving to preserve the places in which they have learned and come to care about.